THE EFFECT OF THE PROJECT-BASED LEARNING MODEL ON THE ABILITY OF RATIONAL COUNTING IN GROUP B AT TK ISLAM AZ-ZAHRAH PALEMBANG - Khana, Ameliya Nada; Andika, Windi Dwi (THUFULA, 2024)
The basic ability of counting in children is important for the development of mathematics at a later stage so the selection of learning models can affect this ability. This study aims to see the effect of rational counting ability in group B of Az-Zahrah Islamic Kindergarten through a project-based learning model. The type of research used is pre-experiment with a shot case study design. The sampling technique used purposive sampling, namely class B4 with a total of 16 children using posttest and observation which will then be analyzed using a one-sample T-test. The results obtained are that the project-based learning model positively influences the ability of rational counting in group B of Az- Zahrah Palembang Islamic Kindergarten. This can be seen in the child’s score in each aspect, such as rote counting, one-to-one correspondence, counting, and cardinal, which has developed as expected. The results of this research can be an alternative for schools or educators in developing counting skills for group B through project learning.